The Role of School Heads in Developing Teacher Professional Competencies in Ekatama Private Vocational School Pekanbaru - Dewi Indrayeni (Postgraduate School, Universitas Negeri Padang, 2020)
This study aims to determine the role of the principal in fostering the professional competence of teachers at Ekatama SMKS Pekanbaru. This research uses descriptive methods and a qualitative approach. Research data collection techniques using observation, interviews and documentation. The data validity analysis technique was performed by triangulation. The data analysis technique uses the stages of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the role of the principal in fostering the professional competence of teachers at Ekatama SMKS Pekanbaru was as an educator, administrator, supervisor, leader, manager, innovator, and motivator. One of the principal roles is as manager. As a manager, thinks conceptually and analytically, is able to face various problems at school, always tries to be an intermediary in solving problems. To improve the competence of teachers, it is important to carry out a system of testing teacher competencies. The existing regional autonomy policy can be used to conduct teacher competency tests. Competency tests are conducted in order to develop and demonstrate the complete competence of a teacher. The complete competence possessed includes the integration, application of knowledge and skills, as well as interrelated attitudes.